A graph-based framework for analyzing SQL query logs - Wahl, Andreas Maximilian; Endler, Gregor; Schwab, Peter; Rith, Julian; Herbst, Sebastian; Lenz, Richard (1st ACM SIGMOD Joint International Workshop on Graph Data Management Experiences and Systems and Network Data Analytics, GRADES-NDA 2018, 2018)

Crossing an OCEAN of queries: Analyzing SQL query logs with OCEANLog - Wahl, Andreas Maximilian; Endler, Gregor; Schwab, Peter; Herbst, Sebastian; Rith, Julian; Lenz, Richard (30th International Conference on Scientific and Statistical Database Management, SSDBM 2018, 2018)

Speaking in Tongues: SQL Access to NoSQL Systems - Rith, Julian; Lehmayr, Philipp S; Meyer-Wegener, Klaus (Proc. 29th ACM Symp. on Applied Computing (SAC), 2014)
Non-relational data stores, which are usually called NoSQL systems, have become an important class of data management systems. They often outperform the relational systems. Yet there is no common way to interface with NoSQL systems. The Structured Query Language (SQL) has already proven to be useful to provide a uniform query language for all the relational systems. We identify a subset of SQL for access to NoSQL systems. Our extensible middleware translates SQL queries to the query languages of the connected NoSQL systems. The migration between these systems is thereby greatly simplified as well as the comparison of the supported NoSQL systems.
UnivIS-Import:2015-04-16:Pub.2014.tech.IMMD.IMMD6.speaki